2015
DOI: 10.1111/hsc.12188
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease in young patients: challenges faced by black and minority ethnic communities in the UK

Abstract: There is strong evidence indicating that inflammatory bowel disease (IBD) is increasing among black and minority ethnic (BME) communities. Despite this rise in prevalence, there is a paucity of research relating to ethnicity and IBD outside the USA. Furthermore, the symptoms of IBD are reported to start during childhood or adolescence in 20-25% of people with the condition. It is therefore important that young people's experiences of diagnosis, treatment and living with IBD are fully understood to ensure effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(73 citation statements)
references
References 23 publications
(35 reference statements)
2
71
0
Order By: Relevance
“…Food has significant cultural connotations and some of those affected by the condition described the added struggle in maintaining the social norms expected by their cultural/ethnic group. This aspect was particularly emphasised in a study looking into challenges faced by black ethnic minorities living with IBD (Alexakis et al, 2015). Similarly, some patients reported that the condition interfered with their religious eating practices; the same study suggest that more than half of those interviewed could not fast during Ramadan as a consequence of their condition.…”
Section: Dietary Constraintsmentioning
confidence: 99%
“…Food has significant cultural connotations and some of those affected by the condition described the added struggle in maintaining the social norms expected by their cultural/ethnic group. This aspect was particularly emphasised in a study looking into challenges faced by black ethnic minorities living with IBD (Alexakis et al, 2015). Similarly, some patients reported that the condition interfered with their religious eating practices; the same study suggest that more than half of those interviewed could not fast during Ramadan as a consequence of their condition.…”
Section: Dietary Constraintsmentioning
confidence: 99%
“…Concerns about possibly requiring surgery and / or a A c c e p t e d M a n u s c r i p t Manuscript Doi: 10.1093/ecco-jcc/jjy020 support networks in patients with a chronic illness can facilitate effective coping, positively influence health status and improve outcomes of disease [46]. Family support, particularly that provided by parents, plays a vital role in the development of children and adolescents with IBD [47].…”
Section: Health-related Quality Of Life [El3]mentioning
confidence: 99%
“…Seven studies were conducted in the UK (31)(32)(33)(34)(35)(36)(37), seven in the USA (38)(39)(40)(41)(42)(43)(44) and one in Malaysia (45). Study design varied and included six case-controlled studies (34,35,39,40,42,44), three survey-based studies (32,33,38,41,43), three qualitative studies (31,36,37), and one cohort study (45); focussing on IBD (31,(33)(34)(35)(36)(37)(39)(40)(41)(42)44), IBS (43,45), prostate cancer (including bowel-related side-effects of treatment) (38) and coeliac disease (32). Studies recruited participants from various ethnic minority groups including South Asians, African Americans, Blacks, Hispanics, and Chinese.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Based on CASP and CEBMa quality criteria, there were seven good (four star) quality studies (31,(35)(36)(37)40,42,45), and eight moderately good (three star) quality studies (33,34,38,39,41,43,44).…”
Section: Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation